1979
DOI: 10.1093/ije/8.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Risk Factor Distributions, Food Habits and Coronary Heart Disease Mortality and Morbidity in Belgium

Abstract: Belgium can be divided in 4 major geographical areas: two Dutch speaking areas in the north (Campine and Flanders), a French speaking area in the south (Wallonia) and the Brussels area in between. Significant differences in mean serum cholesterol levels were observed with the lowest level in Campine, intermediate in Flanders and Brussels, and the highest level in Wallonia. Similar differences were observed in the prevalence of CHD and mortality from CHD is also higher in the French speaking part of the country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
1
22
1
Order By: Relevance
“…Results of previous epidemiological studies, conducted primarily in the area of cardiovascular disease [1][2][3][4][5][6], have shown that these cultural differences are accompanied by a significantly higher morbidity and mortality rate in Wallonia as compared to Flanders. These differences in health experience have by some authors been explained on the basis of differences in lifestyle between the two populations and indeed also by different eating profiles [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Results of previous epidemiological studies, conducted primarily in the area of cardiovascular disease [1][2][3][4][5][6], have shown that these cultural differences are accompanied by a significantly higher morbidity and mortality rate in Wallonia as compared to Flanders. These differences in health experience have by some authors been explained on the basis of differences in lifestyle between the two populations and indeed also by different eating profiles [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The potential impact of intake of certain dietary components on heart disease mortality is of special interest since coronary heart disease is the leading cause of death in the United States [I] and diet has been associated with coronary heart disease in humans [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…During the late 1960s and the 1970s consumption of soft margarines showed a tremendous increase [1], The consumption of saturated oils de creased also during the same period. The P/S ratio showed an increase during the late 1960s and 1970s.…”
Section: Changes In Life-style and Risk Factorsmentioning
confidence: 95%
“…No hard epidemiological data are avail able for the 1950s but during the 1960s and more so during the 1970s, butter consump tion decreased in Belgium [1]. During the late 1960s and the 1970s consumption of soft margarines showed a tremendous increase [1], The consumption of saturated oils de creased also during the same period.…”
Section: Changes In Life-style and Risk Factorsmentioning
confidence: 99%